2011
DOI: 10.1038/ncomms1532
|View full text |Cite
|
Sign up to set email alerts
|

miR-137 forms a regulatory loop with nuclear receptor TLX and LSD1 in neural stem cells

Abstract: miR-137 is a brain-enriched microRNA. Its role in neural development remains unknown. Here we show that miR-137 plays an essential role in controlling embryonic neural stem cell fate determination. miR-137 negatively regulates cell proliferation and accelerates neural differentiation of embryonic neural stem cells. In addition, we show that histone demethylase LSD1, a transcriptional co-repressor of nuclear receptor TLX, is a downstream target of miR-137. In utero electroporation of miR-137 in embryonic mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
232
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(247 citation statements)
references
References 33 publications
5
232
2
Order By: Relevance
“…A number of studies have demonstrated the feasibility of this approach. For example, miR-137 mimics negatively regulate neural stem cell proliferation [120]. Additionally, miR-132 mimics have been shown to block ocular dominance plasticity produced by monocular deprivation when delivered to the mouse visual cortex [121].…”
Section: Microrna Therapymentioning
confidence: 99%
“…A number of studies have demonstrated the feasibility of this approach. For example, miR-137 mimics negatively regulate neural stem cell proliferation [120]. Additionally, miR-132 mimics have been shown to block ocular dominance plasticity produced by monocular deprivation when delivered to the mouse visual cortex [121].…”
Section: Microrna Therapymentioning
confidence: 99%
“…The overexpression of TRIM32 induces neuronal differentiation, whereas the inhibition of TRIM32 preserves the self-renewal capability of neural progenitor cells. The miRNA miR-137 is essential for embryonic NSC fate decisions; the overexpression of miR-137 inhibits NSC proliferation and induces accelerated differentiation by suppressing histone lysinespecific demethylase 1 (LSD1), a co-transcription factor of TLX [108] . Additionally, miR-137, which mediates epigenetic proteins such as MeCP2 (a DNA methylCpG-binding protein), Ezh2, and Polycomb group (PcG) protein, regulates the balance of NSC proliferation and differentiation in adult neurogenesis.…”
Section: Neuronal Differentiationmentioning
confidence: 99%
“…abundant in the brain, has an important role in controlling embryonic neural stem cell fate determination (32). The downregulated expression of miR-137 in brain cancer stem cells is necessary for self-renewal in glioma stem cells (33,34).…”
mentioning
confidence: 99%